2019
DOI: 10.14814/phy2.13983
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous sclerosis complex exhibits a new renal cystogenic mechanism

Abstract: Tuberous sclerosis complex (TSC) is a tumor predisposition syndrome with significant renal cystic and solid tumor disease. While the most common renal tumor in TSC, the angiomyolipoma, exhibits a loss of heterozygosity associated with disease, we have discovered that the renal cystic epithelium is composed of type A intercalated cells that have an intact Tsc gene that have been induced to exhibit Tsc‐mutant disease phenotype. This mechanism appears to be different than that for ADPKD. The murine models describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 100 publications
(192 reference statements)
6
63
0
Order By: Relevance
“…The TSC cystic disease can manifest as one or more of at least five patterns of disease [1], and appears to have a very novel cystogenic mechanism involving the renal tubular cells [14]. In a previous study, we reported that the loss of Tsc2 gene in a mouse renal principal cell affected the phenotype of intercalated cell causing an enhanced mTORC1 activity, thus leading to renal cystogenesis likely via an EV-dependent pathway [14] ( Figure 5). To elucidate our hypothesis, we utilized a well characterized in vitro model.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The TSC cystic disease can manifest as one or more of at least five patterns of disease [1], and appears to have a very novel cystogenic mechanism involving the renal tubular cells [14]. In a previous study, we reported that the loss of Tsc2 gene in a mouse renal principal cell affected the phenotype of intercalated cell causing an enhanced mTORC1 activity, thus leading to renal cystogenesis likely via an EV-dependent pathway [14] ( Figure 5). To elucidate our hypothesis, we utilized a well characterized in vitro model.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of TSC patient develop some form of kidney cyst during their life time but the exact mechanism of kidney cystogenesis in tuberous sclerosis complex is unknown [20]. The TSC cystic disease can manifest as one or more of at least five patterns of disease [1], and appears to have a very novel cystogenic mechanism involving the renal tubular cells [14]. In a previous study, we reported that the loss of Tsc2 gene in a mouse renal principal cell affected the phenotype of intercalated cell causing an enhanced mTORC1 activity, thus leading to renal cystogenesis likely via an EV-dependent pathway [14] ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations